Studying the characteristics of expander-generator units at natural gas pressure reduction points - Abdurahim D. Taslimov; Arsen A. Mukolyants; Jonibek M. Nizomov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: the work is conditioned by the need to study the characteristics of expander-generator units and choose the optimal method of heating gas at the inlet to the expander-generator unit, which largely determines the specific fuel consumption for electricity generation. Various parameters of the expander-generator unit used as autonomous installations for remote gas-distribution stations and gas-control points are analyzed, taking into account the methods of heating gas before gas expansion, such as the use of boilers and exhaust gases from gas turbine unit. Calculations have shown that with low heating, it is preferable to use heating in the boiler, and with an increase in the gas heating temperature, it becomes economically more profitable to use flue gases from a gas turbine unit. Aim: to choose the optimal method of heating gas using a specialized boiler or gas turbine unit, which allows to increase the efficiency of the EGU and reduce the cost of electricity production, which is the main factor when deciding on the EGU at the enterprise Methods: in the work, an integrated method was used to solve the tasks set, including theoretical methods of technical thermodynamics and experimental approaches. The analysis of the current state of theory and practice has been carried out, experiments have also been performed on a full-scale model of a reduction line with an adjustable turbine-type expander. Results: the results obtained for different heating options showed that the highest power is provided by the use of flue gases from a gas turbine installation for gas heating. An analysis of the specific fuel consumption for electricity production at different gas pressures and heating temperatures showed that with a small heating, it is more profitable to use heating in the boiler, whereas with an increase in the gas heating temperature, the use of flue gases from a gas turbine installation becomes more economically feasible.